Shape of the Delta baryon in a covariant spectator quark model - Ramalho, Gilberto (2012)
Using a covariant spectator quark model that describes the recent lattice QCD data for the electromagnetic form factors and all available experimental data on gamma N --> Delta transitions, we analyze the charge and magnetic dipole distributions of the Delta baryon and discuss its shape. We conclude that the quadrupole moment of the Delta is a good indicator of the deformation and that the Delta+ charge distribution has an oblate shape. We also calculate transverse moments and find that they do not lead to unambiguous conclusions about the underlying shape.